1980
DOI: 10.1530/acta.0.0940038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propranolol and atenolol on plasma and urinary cyclic adenosine 3′,5′-monophosphate in hyperthyroid patients

Abstract: Supine and upright plasma concentrations and the urinary excretion of cyclic adenosine 3\ m=' \ , 5\ m=' \ \ x =r eq-\ monophosphate (cAMP) were studied in 26hyper t hyr oid patients before and during treatment for 3\p=n-\6 days and one month with a non-selective (propranolol, n = 13) or a selective \ g = b \ -l -a d r e n e r g i c antagonist (atenolol, n = 13). Before treatment supine and upright plasma concentrations of cAMP were elevated compared to healthy controls and compared to a re-investigation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Raised plasma cyclic AMP levels have been reported in hyperthyroidism and may serve as indirect proof of increased adrenoceptor activity (35-37). Treatment with both propranolol and the selective@, -adrenoceptor blocking drug atenolol induced clinical amelioration and concomitantly reduced plasma cyclic AMP levels, although plasma cyclic AMP did not reach normal levels (37). Some recent studies have shown that the other selective P,-adrenoceptor blocking drug, metoprolol, effectively controls many clinical manifestations of hyperthyroidism (38,39).…”
Section: Thyroid Hormones May Alter Adrenoceptor Activitymentioning
confidence: 99%
“…Raised plasma cyclic AMP levels have been reported in hyperthyroidism and may serve as indirect proof of increased adrenoceptor activity (35-37). Treatment with both propranolol and the selective@, -adrenoceptor blocking drug atenolol induced clinical amelioration and concomitantly reduced plasma cyclic AMP levels, although plasma cyclic AMP did not reach normal levels (37). Some recent studies have shown that the other selective P,-adrenoceptor blocking drug, metoprolol, effectively controls many clinical manifestations of hyperthyroidism (38,39).…”
Section: Thyroid Hormones May Alter Adrenoceptor Activitymentioning
confidence: 99%